Refinement Economic Management Method Based on Management Accounting - Xi Lun; Tian Wang; Mi Zhang; Yining Wang (Discrete Dynamics in Nature and Society)
The economic strength of a country is the external manifestation of its comprehensive national strength. In order to increase a country’s international influence, it must strengthen its own economic development. China’s economy is in a period of rapid development. At this stage, enterprise development is an important factor in promoting steady economic growth. However, economic management plays an important role in the development of an enterprise. Therefore, how to use effective economic management methods to promote the development of enterprises is very important. This method helps to enhance the competitiveness of enterprises and improve the economic efficiency of enterprises. This approach needs to get people’s attention. For productive enterprises, the biggest problem is that the economic benefits are not up to expectations. In addition, spending costs are always well over budget. In fact, this has a lot to do with business management. Before the market, economic system was reformed. The comprehensive management of productive enterprises is mostly extensive management. This makes the economic costs of certain links and details out of control. Therefore, effective management of the economy of a productive enterprise is critical. Although productive enterprises cannot be said to be highly profitable, their economic benefits are at least achievable. For productive enterprises, the most effective management method for the economy is refined management. This article starts from the perspective of improving the speed of enterprise development. Specifically, the starting point is to promote the improvement of the country’s comprehensive national strength. The article analyzes the inherent relationship between economic management and enterprise development, hoping it can provide positive help for China’s social and economic progress.